A Systematic Overview of Decision-Making on Public Transport Systems Using Bibliometric Analysis on Vosviewer - Sahin Süleyman Nurullah Adahi (Transport and Telecommunication, 2023)
From the perspectives of users, operators, and the community, decision making for public transportation is regarded as one of the most crucial characteristics to assess quality, ease and preferable. Studies on the decision-making for public transportation have been published. Comprehensive and quantitative investigations are lacking, nevertheless. Additionally, the Scopus database contains very few assessments of public transport integration. The current evaluation was carried out to provide scholars and practitioners with the most recent updates of papers on public transport and decision-making over the last 18 years (between 2005 and 2023), to allay their worries and address their inquiries about better public transport systems. The purpose of this bibliometric analysis and the overview is to encourage future research and collaboration by illuminating the idea of transport decision making studies, highlighting the paucity of relevant works, and providing a summary of the most productive nations, journals, and institutions in the field. A bibliometric analysis of the publications on public transportation and decision-making obtained from the Scopus database was carried out using the VOSviewer software. This allowed researchers to trace the historical and annual records of publications related to decision making covering the top countries, institutions, journals, most frequently used keywords, authors, citation network analysis, and most cited publications. The analysis’s findings identify the indications and interesting issues spots as well as the publications’ remarkable annual rise in decision-making on public transportation systems.